Student readiness towards online learning during Movement Control Order (MCO) in Malaysia : a descriptive analysis - Mohd Shahrul Nizam Mohd Danuri; Hafiz Mohd Radzi; Rohizah Abd Rahman (Penerbit Universiti Kebangsaan Malaysia, 2021)
This research showed a descriptive analysis on student readiness towards online learning during movement control order (MCO) due to pandemic covid-19. The readiness of the students’ needs to be studied due to the new normal which take an immediate effect and change our lifestyle including the way of learning. The focus of this research was on readiness elements such as technology access quality and facility, online learning time management, skills, tools, and online learning system. We also included additional questions about the response towards learning, if the movement control order period extended and response to the post (after) covid-19 events. This research design was using a quantitative approach through questionnaire survey that has been distributed online to the students of Kolej Universiti Islam Antarabangsa Selangor (KUIS). A total of 2208 respondents answered the questions and analyzed statistically. The results found that the students’ readiness was in moderate level due to the pandemic of covid-19. The lecturers must be more creative and flexible in term of knowledge delivery in the new normal of learning environment.